Evaluation of an online-based self-help program for patients with panic disorder: a randomized controlled trial - Lalk, Christopher; Väth, Teresa; Hanraths, Sofie; Prüßner, Luise; Timm, Christina; Hartmann, Steffen; Barnow, Sven; Rubel, Julian (PsyArXiv preprints, 2023)
Objectives: The present study evaluated the effectiveness of a minimally-guided online self-help intervention for panic disorder with or without agoraphobia. As our primary hypotheses, we expected the intervention to improve both panic symptoms and well-being. - Methods: German-speaking patients (N = 156) between 18 and 65 with internet access and a diagnosis of panic disorder or agoraphobia with panic disorder were recruited for this randomized controlled trial. The intervention group (N = 84) received access to a 12-week online self-help program. The waitlist control group (N = 72) received no intervention during the study period but was offered the prospect of using the program after 12 weeks. - Results: Changes in PAS revealed a significant effect in favor of the intervention group (t (df = 110.1) = -2.22, padj = .027) with a small to moderate effect size (d = -0.37, 95%-CI: -0.70; -0.04). No significant effect was found for the second primary outcome WHO-5 (t (df = 149.8) = 1.35, padj = .088) or the secondary outcomes functioning, mental health literacy, working ability and healthcare use). - Conclusions: The presented online intervention can help reduce the core symptomatology of panic disorder with or without agoraphobia. Diminished effects may be due to higher illness burden in the intervention group and possibly the COVID pandemic which caused unique challenges to patients suffering from panic disorder. Regarding well-being and the secondary outcomes, superiority towards the control group was not established. Therefore, further research and intervention adaptations may be warranted to improve these outcomes.
Gesehen am 13.06.2024